Assessment of beverage consumption by young adults in Saudi Arabia - Md. Ashraful Islam; Aseel Fuad Al-karasneh; Ahmed Bin Hussain; Ali Muhanna; Taher Albu-hulayqah; Atta Abbas Naqvi; Muhammad Shahid Iqbal; Maryam Farooqui; Mahmoud E. Elrggal; Mansour Adam Mahmoud; Abdul Haseeb (Elsevier, 2020)
Objective: The primary objective was to assess beverage consumption pattern and calorie intake among undergraduate students on weekly and daily basis. Secondary objectives were to determine the relationship between demographic variables and beverage intake, assess mean differences in calorie intake between students' groups and, report the predictors of beverage consumption. Methods: A cross-sectional study was conducted for 3 months (January-March 2019) among currently enrolled undergraduate students studying in 8 colleges of a public sector university in Dammam, Saudi Arabia. The study used the Arabic version of Beverage Frequency Questionnaire (BFQ) and collected data through purposive stratified sampling. Total intake in ml and calories in kcals were calculated. Data was analyzed through SPSS version 23 and the study was approved from ethics committee of the university (IRB‐2019‐05‐021). Results: A total of 507 students responded to the survey. The average volume of sugar sweetened beverages (SSBs), caffeine containing beverage (CCBs) and carbonated beverages (CarBs) consumed was 4.2 L, 4 L and 1.5 L per week and 650.6 ml, 575.2 ml and 224.6 ml per day, respectively. Average daily calorie intake from SSBs, CCBs and CarBs was 187.6 kcals, 87.6 kcals and 52.5 kcals, respectively. Body mass index (BMI) was significantly related to CCB (ρ = 0.130) and CarBs (ρ = 0.100) intake (mL) (p < 0.05). Mean difference in calorie intake was mostly significant (p < 0.05) when accounted for students' demographics, gender, BMI, residence, illness and, examination time, in case of SSBs, CCBs, CarBs and, all beverages. Averge % contribution towards total daily energy expenditure (TDEE) for SSBs, CCBs and CarBs were 10.2%, 6.3% and 2.8%, respectively. Year of study, BMI, residence and illness were predictors of SSBs consumption while BMI, residence and examination time were predictors of CCBs consumption. Gender and BMI were predictors of CarBs intake. Conclusion: There was a high consumption of beverages in students that was related to their demographic characteristics. There is a need to create awareness among the students regarding the detrimental effects of chronic consumption of these beverages.